Interpretations of the Prometheus myth in Lithuanian Pre-Soviet, Soviet, and Post-Soviet literature (Colloquia Comparativa Litterarum, 2025)
The article uses comparative and history of ideas methods to review and summarise the inclusion of the universal Prometheus myth in Lithuanian literature. The relevance of this myth began to emerge in the social context of the late 19th century, when the Lithuanian nation was embracing the ideology of nationalism, was searching for its place in political history, and had begun a smooth process of cultural development. The myth, image, and symbol of Prometheus, with new meanings being given to it, has been relevant to Lithuanian authors throughout the entire period of one and a half hundred years in question: from 1883 (when the first periodical Auszra appeared) till 2023. The article presents the most important authors of each period and their works dealing with Promethean themes, as well as the general cultural, literary, and ideological context that conditioned the choice and goals of each author.
Keywords: myth of Prometheus; Lithuanian literature; Pre-War, Inter-War, Soviet, and Post-Soviet periods; intertextuality